Acute hyperlipidemic pancreatitis in a pregnant woman - Hang, Ying (Second Affiliated Hospital of Zhejiang University School of Medicine, 2013)
BACKGROUND: Acute pancreatitis is a serious complication during pregnancy, however the incidence of hyperlipidemia induced by pancreatitis is lower. METHODS: We treated a pregnant woman with hypertriglyceridemia-associated acute gestational pancreatitis who simultaneously developed hypoxemic acute respiratory failure (ARF). RESULTS: The woman was successfully treated through noninvasive positive pressure ventilation (NPPV), emergent caesarean delivery, drainage of chylous ascites, and peritoneal lavage. CONCLUSION: The signs and symptoms of ARF were greatly improved in this patient after NPPV and conventional therapies. Early NPPV may be related to good prognosis of the disease.